Enrobing Ceremony for Judges Thomas Harris, Steven Vartabedian, Edward Sarkisian, Jr. and Lawrence Jones at Fresno's Veterans Memorial Auditorium - Watkins, Howard::::::::: (1987)
Judge Robert Mardikian administering oath of office to Lawrence Jones with wife Nancy Kopps looking on